Adultery [compact disc, unabridged] - Coelho, Paulo (Books on Tape : Random House Audio, 2014)
A woman in her thirties begins to question the routine and predictability of her days. In everybody's eyes, she has a perfect life: happy marriage, children, and a career. Yet what she feels is an enormous apathy. All that changes when she encounters a successful politician who had, years earlier, been her high school boyfriend. As she rediscovers the passion missing from her life, she will face a life-altering choice.